PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN EDUCANDY GAME TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK - Yayang Agustin, Grechia; Izzatika, Amrina; Fitriadi; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem of this research was the low learning outcomes of fourth-grade students in the IPAS subject. This research aimed to determine the effect of the Discovery Learning model assisted by Educandy Game on students’ IPAS learning outcomes. This research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The population of this research consisted of 112 students, while the sample consisted of 56 students from classes IV C and IV D. Data were collected through test and non-test techniques. The hypothesis was tested using simple linear regression analysis. The results showed that the significance value was 0,025 < 0,05, indicating that the Discovery Learning model assisted by Educandy Game had a positive and significant effect on the IPAS learning outcomes of fourth-grade students at SD Negeri 3 Perumnas Way Kandis.